2019
DOI: 10.1186/s40814-019-0501-y
|View full text |Cite
|
Sign up to set email alerts
|

A virtual reality intervention for fear of movement for Veterans with chronic pain: protocol for a feasibility study

Abstract: BackgroundA key concern for people with chronic pain is experiencing increased pain and/or re-injury. Consequently, individuals with chronic pain can develop a maladaptive fear of movement that leads to adverse functional consequences. A primary goal of chronic pain rehabilitation is re-engagement in feared movements through exposure. This is often challenging since safe movement can be uncomfortable. Virtual environments provide a promising opportunity to safely and gradually expose Veterans to movements that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…The psychosocial variables also showed significant changes for both groups, especially in the VR group. For the fear-avoidance beliefs, in 2019 Fowler et al [13] indicated that the use of VR on elderly people with a fear of movement showed positive results when the treatment matched the patient's level of functioning. There was a progression in intensity so that the patients presented a positive perception which presented better benefits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The psychosocial variables also showed significant changes for both groups, especially in the VR group. For the fear-avoidance beliefs, in 2019 Fowler et al [13] indicated that the use of VR on elderly people with a fear of movement showed positive results when the treatment matched the patient's level of functioning. There was a progression in intensity so that the patients presented a positive perception which presented better benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding kinesiophobia, we found that it was the only variable to have significantly improved compared to the exercise group, especially at 3 months follow-up, and was considered as an effective tool for reducing fear of movement. Other studies have found that VR reduces kinesiophobia in patients with chronic spinal pain which was associated with an increase in function [13,67,72]. In 2020, Martínez et al concluded on a narrative review that the participants' physical condition and cognitive and emotional characteristics should be considered before implementing interventions that employ movement representation techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this, these individuals will tend to avoid movement and even physical activities altogether (Alazba, Al-Khalifa & AlSobayel, 2018). By addressing this fear of movement, VR has the OT's ROLE IN PAIN MANAGEMENT USING VIRTUAL REALITY ability to alter one's pain perception, thereby allowing them to not only move, but thrive in a less painful environment (Fowler, Ballistrea, Mazzone, Martin, Kaplan, Kip, Murphy, & Winkler, 2019). Garcia-Palacios et al (2015) explored the potential use of VR as a behavioral intervention for managing pain and addressing the fear of movement.…”
Section: Introductionmentioning
confidence: 99%
“…By distracting pain and facilitating purposeful movement, VR can significantly reduce one's risk for greater functional disability, improve their ability to perform desired activities, and more importantly, improve their coping ability so that they can better manage their pain experience (Fowler et al, 2019;Alazba, Al-Khalifa & AlSobayel, 2018). However, like opioids, OT's ROLE IN PAIN MANAGEMENT USING VIRTUAL REALITY 8 the use of virtual reality alone cannot effectively improve an individual's pain management.…”
Section: Introductionmentioning
confidence: 99%